P-113 The role of the research nurse in the hospice. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Perry, Rachel; MacArtney, John; Bache, Sarah; Prew, Sandra
Abstract : Background: The NIHR and Charities Consortium for Hospice and Community Research have stated that the goal for all hospices is to be research active and recruit by 2022. The role of the Research Nurse in the hospice setting is still relatively new. Aims: This poster aims to share the experiences and lessons learnt by a Research Nurse who is in a unique position of being based within two hospices in the West Midlands. Building capability and research capacity: At one hospice, the Research Nurse works alongside the Senior Research Fellow. The learning and development gained from this relationship has fostered confidence and skills which enable the Research Nurse to carry out her role at a second hospice alongside the Nurse Consultant. The role is funded and supported by West Midlands CRN. This innovative way of working has provided many opportunities for the hospices to become further engaged in research, including portfolio studies. It has enabled the sharing of ideas across hospices, the development of recruitment opportunities and the opportunity to ensure research is embedded into everyday practice in both hospices. Key outcomes of the collaborations have been: Facilitating engagement with research at the hospices; Being a bridge between the often–competing pressures of clinical care and research, by finding novel solutions to obstacles; Empowering staff by encouraging them to be a part of research in everyday practice. Being a resource for staff by supporting them with academic assignments, producing posters for conferences and disseminating research findings; Developing a research culture by sharing good practice across organisations. Building future research capacity Ongoing and future challenges for the Research Nurse over the next year include: To further develop a research culture in both hospices; Increase staff confidence and awareness of research activity in both hospices; Ensure patients, families and staff are given further opportunities to participate in research.